Analysis of antibiotic sensitivity of E. coli in patients with chronic calculous pyelonephritis - N G Kulchenko; M A Vekilyan (RUDN Journal of Medicine, 2016)
There are substantial differences in the sensitivity of uropathogens to antimicrobial agents in different countries and regions of the same country. So important is a regular review of the antimicrobial activity. The purpose of the study is to improve the results of treatment of patients with complicated calculous pyelonephritis. The materials and methods. Conducted retrospective pharmaco-epidemiological analysis of medical records of 91 patients who were treated in 2015, in a hospital of Volgograd city. All patients underwent standard clinical examination, with mandatory bacteriological urine analysis, ultrasound examination of kidneys. Results. To date, 89.4% of patients with chronic calculous pyelonephritis have high sensitivity of the main causative agents of infection to cephalosporins of the third and fourth generation, 86.4% - to the protected beta-lactam penicillins (amoxicillin/clavulanate) and 97,7% - to the derived carbapenemov (p < 0.05). Conclusions. Regular monitoring of local and regional antibiotic sensitivity and resistance of uropathogens is required.